Rapid detection of antibiotic resistance in Salmonella with screen printed carbon electrodes - Ren, Yijing; Ji, Jian; Sun, Jiadi; Pi, Fuwei; Zhang, Yinzhi; Sun, Xiulan (Journal of solid state electrochemistry, 2020)
Salmonella , one of the most common foodborne pathogens, poses a serious threat to human health. In recent years, the antibiotic resistance of Salmonella has become serious as well, which has strengthened the harm of Salmonella to human health. In this paper, a simple and effective electrochemical approach was developed to obtain profile of the antimicrobial susceptibility. Screen-printed carbon electrodes (SPCEs) were used to detect various concentrations of target bacteria at the same time, which have good stability, low cost, and easy mass production. The electroactive redox, resazurin, was used to monitor levels of metabolically active bacteria. As a demonstration, the antibacterial effect of ofloxacin and penicillin on Salmonella gallinarum ( S. gallinarum ) isolates was evaluated, and the minimum inhibitory concentration (MIC) was measured as well. In the real sample measurement, the MIC obtained was similar to that obtained by conventional antimicrobial susceptibility testing (AST). In this assay, bacterial activity was quantified sensitively and accurately, and the detection time was greatly reduced compared with conventional AST (16–20 h), which means that metabolic capacity of live bacteria could be observed after 1 h of incubation. We were able to clearly detect bacteria above 10 2 CFU/m. This method aims to nonspecific and can be widely applied to the detection of a variety of drug-resistant bacteria, providing an experimental basis for the rational use of antibiotics and bacterial resistance mechanisms.